A CASE OF JUVENILE GIANT FIBROADENOMA - Dhungana, Saroj; Kumar Mandal, Rajesh; Acharya, Bishal; Giri, Barsha; Shrestha, Shreya; Dulal, Saujan (Journal of Chitwan Medical College, 2024)
Fibroadenomas that measure more than 5 cm in diameter or 500g in weight are known as Giant Fibroadenoma(GF). The most frequent cause of unilateral breast enlargement in teenagers and a rare variant of fibroadenoma, juvenile giant fibroadenoma (JGF), accounts for 2% to 10% of all breast fibroadenomas. GF requires a full surgical excision due to its rapid growth and diagnostic challenges. We present a case of Juvenile Giant fibroadenoma in 15 years female. The lesion was excised using Modified round block technique by Benelli. The post-operative outcome was satisfactory. The round block technique by Benelli is one of the modality for excision of giant fibroadenoma. This technique has better cosmetic and functional outcome as it produces a discrete scar and a more regular breast contour.